2020
DOI: 10.47102/annals-acadmedsg.202085
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Critical Role of Angiotensin 1-7 in ACE2 Modulation

Abstract: With the declaration of Novel Coronavirus Disease 2019 (COVID-19) as pandemic by World Health Organization (WHO), many countries have taken drastic measure to enforce movement control to curb COVID-19 outbreak. On 23 January 2020, it was reported that Malaysia had 4 patients suspected to have contracted the COVID-19. On the same day, Singapore confirmed its first case of COVID-19. 1 The first confirmed COVID-19 case reported in Malaysia was on 24 January 2020. To date, WHO has reported a total of 5.6 million c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…As this pandemic continues to evolve, researchers are learning more about SARS-CoV-2 every day, including the fact that it can be transmitted from symptomatic, presymptomatic and asymptomatic people infected with COVID-19 [4] . Studies have shown that COVID-19 is primarily transmitted from symptomatic people to people who are in close contact through respiratory droplets, by direct contact with infected persons or by contact with contaminated objects and surfaces [5] .…”
Section: Introductionmentioning
confidence: 99%
“…As this pandemic continues to evolve, researchers are learning more about SARS-CoV-2 every day, including the fact that it can be transmitted from symptomatic, presymptomatic and asymptomatic people infected with COVID-19 [4] . Studies have shown that COVID-19 is primarily transmitted from symptomatic people to people who are in close contact through respiratory droplets, by direct contact with infected persons or by contact with contaminated objects and surfaces [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Ang(1-9) mediates its actions via the AT 2 R and produces the protective responses such as anti-fibrotic and anti-inflammatory effects [ 70 ]. Moreover, Ang(1-7) has been reported to bind to another GPCR, the Mas receptor (MasR), which can exert NO-dependent vasorelaxation and protect against cardiac remodelling; Ang(1-7) also acts as a Ī²-arrestin biased agonist at AT 1 Rs [ 71 , 72 , 73 ]. This induces AT 1 R desensitisation and internalisation, which attenuates the Ang II mediated cardiovascular dysfunction [ 57 ].…”
Section: The Role Of Ace2 In the Raas And Kksmentioning
confidence: 99%
“…The spike glycoprotein at the N-terminal region of SARS-CoV-2 acts as a receptor binding domain which binds to the human angiotensin converting enzyme 2 (ACE2) of the host cell. This leads to fusion between viral and host cell membranes to allow entry of coronavirus into target host cells [ 4 ]. Upon being infected with SARS-CoV-2, patients may present without symptoms or with symptoms, ranging from mild, moderate, severe to critical, with clinical classifications outlined by the Chinese National Health Committee [ 5 ].…”
Section: Introductionmentioning
confidence: 99%